2021
DOI: 10.1051/ro/2019062
|View full text |Cite
|
Sign up to set email alerts
|

Incentive design with customer satisfaction for business process outsourcing: multi-taskvs. multi-agent

Abstract: We study the incentive design decision of a firm that outsources its online marketing and operational business lines to professional external and internal service providers under the principal-agent framework. Customer satisfaction is represented as the composite of the agents' sales and qualitycontrol efforts via the disconfirmation model, and is introduced into the demand model and incentive contracts. Two scenarios corresponding to whether the brand owner delegates business to a single agent or to multiple … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 60 publications
0
2
0
Order By: Relevance
“…To estimate the security value of a SESE fragment, we start first at the estimation of the security value for a process task Sec(a i ) (see Equation (10)) that is calculated according to the number of the environment Env protection nb_CorrectedTH and the number of the threats thr that exist nb_ExistenceTH (see Equations ( 8) and ( 9)). Based on the Sec(a i ) of tasks values that constitute a SESE, we proposed Equation (11) to estimate the SESE security value Sec(SESE), which is expressed in percentage.…”
Section: Securitymentioning
confidence: 99%
See 1 more Smart Citation
“…To estimate the security value of a SESE fragment, we start first at the estimation of the security value for a process task Sec(a i ) (see Equation (10)) that is calculated according to the number of the environment Env protection nb_CorrectedTH and the number of the threats thr that exist nb_ExistenceTH (see Equations ( 8) and ( 9)). Based on the Sec(a i ) of tasks values that constitute a SESE, we proposed Equation (11) to estimate the SESE security value Sec(SESE), which is expressed in percentage.…”
Section: Securitymentioning
confidence: 99%
“…Our extensive literature exercise revealed that most of the existing approaches deal mainly with the decision-making of traditional BPs, such as [7][8][9][10][11][12][13]. Some recent works have addressed the decision-making of the BPs that embedded only the IoT technology (e.g., [14][15][16]).…”
Section: Introductionmentioning
confidence: 99%